수학 학습에 미치는 주요 영향 요인 분석: 선행 연구로부터의 통찰 - 김홍겸; 고호경 (East Asian Mathematical Journal, 2024)
Achieving something in learning is a very important task. Dueto its significance, extensive research has been conducted over a long period to determine what factors influence learning. In the field of mathematics, such research has been continuously carried out, and as a result, it has been revealed that cognitive, affective, and socio-environmental factors influence mathematics learning. However, most of these studies were based on one or two variables, and thus, they did not comprehensively examine the factors affecting mathematics learning. Therefore, this study aims to synthesize the existing research to comprehensively derive the factors influencing mathematics learning.
Keywords: Mathematics Learning; Affective Factor; Cognitive Factor; Socio-Environmental Factor